Characterization of a Thermotolerant Phytase Produced by Rhizopus microsporus var. microsporus Biofilm on an Inert Support Using Sugarcane Bagasse as Carbon Source - Sato, Vanessa Sayuri [UNESP]; Jorge, João Atílio; Guimarães, Luis Henrique Souza [UNESP] (Springer Nature, 2016)
The Rhizopus microsporus var. microsporus biofilm was able to produce increased levels of an extracellular thermotolerant phytase using polyethylene and viscose as an inert support in both modified NBRIP medium and modified Khanna medium containing sugarcane bagasse as the carbon source. The enzyme production was strictly regulated by the phosphorus content with optimal production at 0.5 mM of sodium phytate and KH2PO4. The extracellular phytase, RMPhy1, was purified 4.18-fold with 4.78 % recovery using DEAE-cellulose and CM-cellulose. A single protein band with a molecular mass of 35.4 kDa was obtained when the samples were subjected to 10 % SDS-PAGE. The optimum temperature for activity was 55 °C and the optimum pH was 4.5. R. microsporus var. microsporus phytase exhibited high stability at 30 and 40 °C with a half-life of 115 min at 60 °C. The enzyme activity increased in the presence of Ca2+ and was inhibited by Zn2+, arsenate, and sodium phosphate. Phytase demonstrated high substrate specificity for sodium phytate with Km = 0.72 mM and Vmax = 94.55 U/mg of protein and for p-NPP with Km = 0.04 mM and Vmax = 106.38 U/mg of protein. The enzyme also hydrolyzed ATP, AMPc, glucose 6-phosphate, glucose 1-phosphate, and UDPG. This is the first report on phytase characterization delivered with biofilm technology. The properties of the enzyme account for its high potential for use in biotechnology and the possibility of application in different industrial sectors as feed in the future.
Keywords: Enzyme characterization; Fungal biofilm; Phytase; Rhizopus microsporus